Incidence trends of squamous cell carcinoma of the head and neck (SCCHN) in the aging population––A SEER‐based analysis from 2000 to 2016. (20th July 2021) - Taylor, Melissa A.; Switchenko, Jeffery; Stokes, William; Patel, Mihir R.; McDonald, Mark; Steuer, Conor; Aiken, Ashley; Beitler, Jonathan J.; Shin, Dong M.; Saba, Nabil F.
Abstract: Background: Tobacco and alcohol use are risk factors for Squamous Cell Carcinoma of the Head and Neck (SCCHN); however, there is growing recognition of HPV as a risk factor for SCCHN. HPV‐related SCCHN is thought to affect mostly middle‐aged individuals but as the US population ages, it is important to evaluate the change in incidence of HPV‐ and non‐HPV‐related SCCHN in individuals who are ≥65 years old. Methods: This was a retrospective study using data from a population‐based cancer registry (SEER) to identify individuals ≥65 years old diagnosed with SCCHN between 2000 and 2016 also stratified by sex, race, and birth cohort. The subgroups of HPV‐associated and non‐HPV associated sites were analyzed independently. The incidence per year was calculated and joinpoint detection was used to identity significant changes in incidence trends and annual percent change (APC). Results: For HPV‐associated sites from 2000 to 2016, there was an average annual rate of 10.8 per 100, 000 individuals with an APC of 2.92% ( p  = <0.05). For HPV‐ and non‐HPV‐related SCCHN males had a higher annual rate compared to females, 54.5 versus 18.0 in non‐HPV‐related and 19.1 versus 4.4 in HPV‐related sites. For non‐HPV‐related sites there was a decrease in APC across all stratified groups. For HPV‐related sites there was an increase in APC across all stratified groups, especially males (APC 8.82% 2006–2016 p  < 0.05) and White individuals (APC 8.19% 2006–2016 p  < 0.05). When stratified by birth cohort, HPV‐related SCCHN sites had a higher APC in ages 65–69 (8.38% p  < 0.05) and 70–74 (8.54% p  < 0.05). Conclusion: Among the population ≥65 years old from 2000 to 2016, the incidence rate for HPV‐related SCCHN sites has increased across all stratified groups, especially in White individuals, males, and age groups 65–74. The incidence rate for non‐HPV‐related sites has decreased across all stratified groups during this time. Abstract : This study reports results that are consistent with other studies demonstrating that the prevalence HPV associated of head and neck cancer overall is increasing in the elderly population age ≥65 years. This increase is occurring when stratified by race, sex, and birth cohort however, the White male population is experiencing the most significant annual percent increase in the incidence of HPV‐associated head and neck cancers. HPV‐associated head and neck cancers are no longer a disease associated with younger patients and the increasing prevalence of this disease in the elderly population is important when considering the unique challenges of treatment for this age group.